2022
DOI: 10.3233/wor-211220
|View full text |Cite
|
Sign up to set email alerts
|

‘Art at Safe Homes’: A pioneer study among COVID-19 patients and their treatment team

Abstract: BACKGROUND:The novel coronavirus (COVID-19) has affected mental health all over the world. The resilience of people is heavily influenced by it. OBJECTIVE: This study examined the usage of artistic engagement to overcome stress or anxiety of COVID-19 patients and the treatment team. METHODS:The study was carried out at two safe homes for COVID-19 care in Kolkata, India. Different art and performance activities were implemented like drawing, theatre, poetry and music. All total 42 participants (24 patients and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 53 publications
(49 reference statements)
0
1
0
Order By: Relevance
“…Noticeably, activities such as artistic engagement can improve the level of resilience of individuals and communities (Reed et al, 2020 ). The creative process (e.g., drawing) allows the expression and processing of emotions within group interventions as well as with COVID-19 patients (Bhattacharya et al, 2022 ). Plus, it has been demonstrated that the creative potential represents a protective factor against COVID-19 lockdown stress (D'Anselmo et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Noticeably, activities such as artistic engagement can improve the level of resilience of individuals and communities (Reed et al, 2020 ). The creative process (e.g., drawing) allows the expression and processing of emotions within group interventions as well as with COVID-19 patients (Bhattacharya et al, 2022 ). Plus, it has been demonstrated that the creative potential represents a protective factor against COVID-19 lockdown stress (D'Anselmo et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%